2021
DOI: 10.1055/s-0041-1726091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Enteral Clonidine Taper following Prolonged Dexmedetomidine Exposure in Critically Ill Children

Abstract: The aim of the current study is to evaluate the use of an enteral clonidine transition for the prevention or management of dexmedetomidine withdrawal symptoms in critically ill children not exposed to other continuous infusion sedative agents. A retrospective, single-center study was conducted in patients ≤ 18 years of age admitted to the pediatric intensive care unit who received a continuous infusion of dexmedetomidine for ≥ 24 hours and who were prescribed enteral clonidine within 72 hours of dexmedetomidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Therefore, data gathered from cohorts exposed to only dexmedetomidine or weaned from dexmedetomidine alone are highly valuable for identifying signs and risk factors for dexmedetomidine withdrawal without the confounding effects of opioid or benzodiazepine exposure and/or their concomitant weaning. In the five cohorts without opioid or benzodiazepine exposure or with dexmedetomidine weaning alone (15, 23), withdrawal signs of hypertension, and tachycardia and agitation were still observed, thus supporting the presence of a withdrawal syndrome attributable to dexmedetomidine. While sedation regimens with dexmedetomidine alone may not always be feasible, future studies investigating dexmedetomidine withdrawal must control for these important potential confounding factors in their design or analysis.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Therefore, data gathered from cohorts exposed to only dexmedetomidine or weaned from dexmedetomidine alone are highly valuable for identifying signs and risk factors for dexmedetomidine withdrawal without the confounding effects of opioid or benzodiazepine exposure and/or their concomitant weaning. In the five cohorts without opioid or benzodiazepine exposure or with dexmedetomidine weaning alone (15, 23), withdrawal signs of hypertension, and tachycardia and agitation were still observed, thus supporting the presence of a withdrawal syndrome attributable to dexmedetomidine. While sedation regimens with dexmedetomidine alone may not always be feasible, future studies investigating dexmedetomidine withdrawal must control for these important potential confounding factors in their design or analysis.…”
Section: Discussionmentioning
confidence: 77%
“…Only 11 of the 23 studies provided recommendations on the usage of clonidine in patients being weaned from dexmedetomidine. Of these 11 studies, six reported decreased tachycardia, hypertension, and/or agitation with clonidine use (12, 15, 20, 21, 23, 24). Four studies, comprising a total of 304 patients undergoing dexmedetomidine tapering without clonidine, and 97 patients undergoing dexmedetomidine tapering with concomitant clonidine, directly compared rates of dexmedetomidine withdrawal signs between these two strategies (11, 12, 20, 23).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations